PROTEIN AND ENERGY REQUIREMENT FOR MAINTENANCE AND GROTH OF BALI CATTLE - Mariani, N.P; Mahardika, I G.; Putra, Sentana; Gaga Partama, I.B. (E-Journal of Animal Science Udayana University, 2013)
This experiment was conducted to determine the protein and energy requirement for maintenance and growth of bali cattle. The experiment used randomized completely block design (RCBD), which consisted of five treatments and three weight groups as block. The initial body weight of male bali cattle was 198.67-207.00 kg. The treatments were five rations which composed with different protein and energy content as follows: ration A with 15.42% protein and 4020 kcal GE/kg DM, ration B with 14.74% protein and 3750 kcal GE/kg DM; ration C with 13.11% protein and 3790 kcal GE/kg DM ; ration D with 10.33% protein and 3920 kcal GE/kg DM, and ration E with 10.58% protein and 3530 kcal GE/kg DM. The variables measured were nutrient intake and as well as the calculation of the energy and protein requirement. The results showed that dry matter and energy intake were not significant different, but the highest protein consumption was on A treatment and the lowest was on E treatment (0.77 vs 0.52 kg/d). Requirement of protein and energy for maintenance was 8.23 g/ W0.75/d and 137.85 kcal/W0.75/d, while requirement of protein and energy for growth was 345.25 g/kg body weight gain and 3753.31 kcal/kg body weight gain. Total protein and energy requirements of growing bali cattle could be calculated with the formula PRt = 8.23 W0.75 + 345.25 ?W g / d and ERt = 137.85 W0.75 + 3753.31 ?W kcal/d, where: PRt is total protein requirements; ERt is total energy requirements; W is body weight and ?W is weight gain ).
Keywords: growing bali cattle, protein and energy requirements